The effects of language on the stigmatization and exclusion of returning citizens: Results from a survey experiment - Jackl, Hilary M (Punishment & society, 2023)
Although the use of person-centered language has increased in recent years, its usage remains limited within the field of criminal justice, wherein terms such as ex-offender are frequently used to describe formerly incarcerated individuals. Research suggests that person-centered language matters for public opinion, but prior work has not examined the effect of language on support for the social reintegration of returning citizens. The present research experimentally manipulates the effects of the language used to describe individuals released from incarceration and the race of a hypothetical returning citizen on the following outcomes: negative stereotype endorsement, attitudinal social distance, and support for reintegrative initiatives. I find that person-centered language significantly reduces stigmatization of returning citizens, which ultimately increases support for reintegrative services. These findings suggest that humanizing changes to criminal justice discourse may have the capacity to shift public opinion and create a social context more conducive to reintegration after incarceration.